KESESUAIAN DAN DAYA DUKUNG EKOSISTEM TERUMBU KARANG SEBAGAI KAWASAN WISATA SNORKELING DI PELABUHAN DALAM PERAIRAN TUING KABUPATEN BANGKA - Martin Yuda Paradise; Okto Supratman; Eva Utami; Okto Supratman (Akuatik: Jurnal Sumberdaya Perairan, 2019)
Tuing waters have potential of coastal ecosystems, namely coral reef ecosystems that have their own special attraction as a diversity of marine biotaso it has the potential for marine tourism activities. This study aims to provide information about the suitability level of snorkeling tours in Pelabuh Dalam of Tuing Waters in Bangka Regency. The study was conducted in April-Mei 2019 in the Tuing Waters of Bangka Regency. Reef fish data collection using the Visual Census method and coral reef data collection using the Line Intercept Transect method. Using analysis of Tourism Suitability Index (IKW). The results of the Snorkeling Tourism Suitability Index at Pelabuh Dalam Tuing Beach at stations 1 to station 6 are in the quite appropriate category (S2) when used as a Snorkeling Tourism location, with a value of station 1 of 73.68 (%), station 2 of 57.89 (%), station 3 is 71.93 (%), station 4 is 66.64 (%), station 5 is 70.18 (%) and station 6 is 56.1 (%). The carrying capacity of the Region (DDK) for snorkeling tourism activities at Pelabuh Dalam Tuing Beach is 134 (people / day) with an area of 33.448.037 m² of coral reef utilization.